2022
DOI: 10.1155/2022/1265204
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Auxiliary Information–Based Control Charting Schemes for the Process Dispersion with Application of Glass Manufacturing Industry

Abstract: The hybrid exponentially weighted moving average (HEWMA) control chart is an enhanced version of the EWMA control chart that monitors the process parameters effectively. Similarly, the auxiliary information-based (AIB) EWMA control charts are very efficient for monitoring process parameters. The purpose of this paper is to propose two new control charts for the improved monitoring of process dispersion referred to as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Recently, Haq et al [22] suggested AIB adaptive Crosier CUSUM (ACC AIB ) under fixed and variable sampling intervals and AIB adaptive EWMA (AE AIB ) control charts for the monitoring of PLOS ONE process mean. For more details about adaptive EWMA, hybrid EWMA, and AIB memory control charts, see [23][24][25][26][27] and reference therein.…”
Section: : Introductionmentioning
confidence: 99%
“…Recently, Haq et al [22] suggested AIB adaptive Crosier CUSUM (ACC AIB ) under fixed and variable sampling intervals and AIB adaptive EWMA (AE AIB ) control charts for the monitoring of PLOS ONE process mean. For more details about adaptive EWMA, hybrid EWMA, and AIB memory control charts, see [23][24][25][26][27] and reference therein.…”
Section: : Introductionmentioning
confidence: 99%